Does BCA3 Play a Role in the HIV-1 Replication Cycle? - Rumlová, Michaela; Křížová, Ivana; Zelenka, Jaroslav; Weber, Jan; Ruml, Tomáš (Viruses, 2018)
The cellular role of breast carcinoma-associated protein (BCA3), also known as A-kinase-interacting protein 1 (AKIP-1), is not fully understood. Recently, we reported that full-length, but not C-terminally truncated, BCA3 is incorporated into virions of Mason-Pfizer monkey virus, and that BCA3 enhances HIV-1 protease-induced apoptosis. In the present study, we report that BCA3 is associated with purified and subtilisin-treated HIV particles. Using a combination of immune-based methods and confocal microscopy, we show that the C-terminus of BCA3 is required for packaging into HIV-1 particles. However, we were unable to identify an HIV-1 binding domain for BCA3, and we did not observe any effect of incorporated BCA3 on HIV-1 infectivity. Interestingly, the BCA3 C-terminus was previously identified as a binding site for the catalytic subunit of protein kinase A (PKAc), a cellular protein that is specifically packaged into HIV-1 particles. Based on our analysis of PKAc⁻BCA3 interactions, we suggest that BCA3 incorporation into HIV-1 particles is mediated by its ability to interact with PKAc.
Keywords: Protein Binding; Adaptor Proteins, Signal Transducing; HIV-1; replikace viru; HEK293 buňky; HEK293 Cells; jaderné proteiny; M-PMV; virion; Cyclic AMP-Dependent Protein Kinases; HeLa buňky; vazba proteinů; lidé; Virion; Virus Replication; HeLa Cells; Humans; BCA3; adaptorové proteiny signální transdukční; AKIP-1; PKAc; proteinkinasy závislé na cyklickém AMP; virus incorporation; Nuclear Proteins; Virus Assembly; sestavení viru